ANALISIS EFEKTIFITAS SISTEM PEMENTAUAN PENGENDALIAN DAN PENGAWASAN (SISPANDALWAS) PADA KAWASAN KONSERVASI PERAIRAN DAERAH RAJA AMPAT - Florentina Utriana Bame; Andi Irwan; Wa Ode Likewati; Amiruddin Amiruddin (POLITEKNIK LP3I JAKARTA, 2026)
The Raja Ampat Regional Marine Conservation Area (KKPD) is a global center of marine biodiversity that requires an effective monitoring, control, and surveillance (MCS) system to ensure ecosystem sustainability. This study aims to analyze the effectiveness of the MCS system in KKPD Raja Ampat, identify implementation obstacles, and examine its impact on marine ecosystem sustainability. This research employed a qualitative approach with a case study design. Primary data were collected through in-depth interviews with 15 informants from six stakeholder categories (UPTD managers, law enforcement officers, the Marine and Fisheries Office, local communities and fishermen, tourism operators, and conservation NGOs) and participatory observation. Secondary data included regulations, management reports, statistical data, and relevant literature. Data analysis used Miles, Huberman, and Saldaña’s interactive model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and theory triangulation. The results indicate that MCS effectiveness in KKPD Raja Ampat is partial: ecological monitoring functions reasonably well with NGO partner support, but human activity monitoring remains weak; the control system has an adequate regulatory framework but faces significant implementation gaps; and the surveillance system has limited coverage due to insufficient patrol infrastructure and technology. Key obstacles include resource constraints, institutional coordination, socio-cultural factors, and law enforcement challenges. The impact of MCS effectiveness on the ecosystem is reciprocal, where well-managed areas show healthy ecological conditions, while poorly monitored areas experience degradation. This study recommends strengthening institutional capacity, increasing technology investment, enhancing inter-agency coordination, and developing community participation in KKPD Raja Ampat management.